Primary Appendiceal Adenocarcinoma Presenting with Hematochezia due to the Invading Tumor in the Sigmoid Colon - Tatsuya Suzuki; Yasuhiro Yamamoto; Toshihiko Torigoe; Shoichiro Mizukami; Kengo Shigehara (Case Reports in Surgery)
Primary appendiceal tumors are rare malignancies; some cases have been described to invade other organs, and this represents a very rare clinical condition. We report a case of appendiceal adenocarcinoma invading the sigmoid colon and a review of similar cases. A 69-year-old woman with complaints of hematochezia was admitted to the hospital. Colonoscopy revealed a tumor in the sigmoid colon, which was a well-differentiated tubular adenocarcinoma. A computed tomography scan showed an appendiceal mass that involved the sigmoid colon, suggesting an appendiceal cancer invading the sigmoid colon. Ileocecal resection with extended lymphadenectomy and en bloc resection of the sigmoid colon was performed. The appendiceal tumor involved the sigmoid colon and the terminal ileum. The ileocecal part which included the tumor and the involved sigmoid colon was resected in total. Macroscopic findings showed that the appendiceal tumor made a fistula with the sigmoid colon. Pathological examination revealed that the tumor was a well-differentiated tubular adenocarcinoma that invaded the sigmoid colon. The final pathological stage was T4bN0M0, stage IIC. The patient was discharged from the hospital uneventfully. She was alive without relapse after a 20-month follow-up. Although an appendiceal tumor invading the rectosigmoid region is rare, a preoperative diagnosis can be obtained that facilitates the planning of a suitable surgical procedure: en bloc resection of the ileocecal part and the rectosigmoid part.